Pemodelan Geographically Weighted Negative Binomial Regression (GWNBR) untuk Menganalisis Faktor-Faktor yang Mempengaruhi Jumlah Kasus Baru HIV/AIDS di Pulau Jawa Tahun 2019 - Rifal Miju; Achmad Prasetyo (Seminar Nasional Official Statistics, 2021)
One of the problems in the health sector is the HIV/AIDS epidemic. The country of Indonesia itself is in the 5th most at risk of HIV/AIDS in the Asian continent (Ministry of Health of the Republic of Indonesia, 2013). The island of Java as the area with the highest number of cases with a population of about 56 percent of the total population of Indonesia. The purposes of this study are to find out the general description of the distribution of HIV/AIDS in Java and to identify the influencing factors by considering the effect of regional proximity. The results of the analysis show that the distribution of the number of HIV/AIDS cases is relatively clustered between regions that have high and low number of cases, this indicates a spatial effect between regions. Then the GWNBR shows that there are differences in the significance of the variables in each region and forms 9 groups of regency/municipality based on the significant variables.